The Fundamental Interactions Between Hydrogen and group III-VI and IV-VI van der Waals Crystals - Felton, James (2023)
Eighteen years since the exfoliation of graphene was first demonstrated, van der Waals (vdW) materials have attracted incredible fundamental and applied research interest. The sustained level of interest can be attributed to the unique properties and the diversity of vdW crystals, which can be readily exfoliated via the simple method first used for graphene. Over the same period, a renewed wave of hydrogen research has emerged with the aim of reducing greenhouse gas emissions. As such, the two fields have often intersected, with the properties of vdW materials often well suited to applications in hydrogen storage, sensing, generation and purification. This PhD considers the fundamental interactions of vdW materials with hydrogen. Specifically, the focus of this work is on the interactions with the vdW semiconductors SnS2, SnS, γ-InSe and ϵ-GaSe. It was found that SnS2 can be converted to SnS upon hydrogen exposure, producing a heterostructure with surprising uniformity and a step-like interface. Exposure of γ-InSe to H-ions modifies its optical and vibrational properties, whilst theoretical studies reveal an exciting modification to the phonon modes upon H2 incorporation. Finally, water exposed ϵ-GaSe is partially oxidised, modifying its electronic band structure, relevant to solar water splitting applications. These results are of fundamental interest and relevant to both hydrogen and semiconductor technologies, ranging from engineered vdW heterostructures and optoelectronics, to hydrogen storage and generation.